Enhancing electrical outputs of the fuel cells with Geobacter sulferreducens by overexpressing nanowire proteins. Issue 3 (3rd August 2022) - Wang, Zhigao; Hu, Yidan; Dong, Yiran; Shi, Liang; Jiang, Yongguang
Abstract: Protein nanowires are critical electroactive components for electron transfer of Geobacter sulfurreducens biofilm. To determine the applicability of the nanowire proteins in improving bioelectricity production, their genes including pilA, omcZ, omcS and omcT were overexpressed in G. sulfurreducens . The voltage outputs of the constructed strains were higher than that of the control strain with the empty vector (0.470–0.578 vs. 0.355 V) in microbial fuel cells (MFCs). As a result, the power density of the constructed strains (i.e. 1.39–1.58 W m −2 ) also increased by 2.62‐ to 2.97‐fold as compared to that of the control strain. Overexpression of nanowire proteins also improved biofilm formation on electrodes with increased protein amount and thickness of biofilms. The normalized power outputs of the constructed strains were 0.18–0.20 W g −1 that increased by 74% to 93% from that of the control strain. Bioelectrochemical analyses further revealed that the biofilms and MFCs with the constructed strains had stronger electroactivity and smaller internal resistance, respectively. Collectively, these results demonstrate for the first time that overexpression of nanowire proteins increases the biomass and electroactivity of anode‐attached microbial biofilms. Moreover, this study provides a new way for enhancing the electrical outputs of MFCs. Abstract : Geobacter sulfurreducens strains with overexpressed nanowire proteins were constructed and used as electricigens in microbial fuel cells. Enhanced electrical outputs based on promoting biofilm formation on anode demonstrated that nanowire proteins are promising genetic tools to improve electrochemical performance of microbes for bioelectricity production.